2019
DOI: 10.1002/jnm.2627
|View full text |Cite
|
Sign up to set email alerts
|

Theory of characteristic modes for lossy structures: Formulation and interpretation of eigenvalues

Abstract: Volume integral equation (VIE) and surface integral equation (SIE) based characteristic mode (CM) formulations are investigated in the case of lossy objects. Imperfectly conducting metallic structures modelled with an impedance boundary condition and lossy dielectric bodies are considered. Two types of CM formulations are studied. In the first one, the generalized eigenvalue equation is expressed in terms of the Hermitian parts of the integral operators. In the second one, the weighting operator of the eigenva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…This formulation agrees with the first formulation of [10], and the eigenvalues have the following physical interpretation [18] λ n = P reac n…”
Section: A Radiated Power-based Formulationsupporting
confidence: 78%
See 1 more Smart Citation
“…This formulation agrees with the first formulation of [10], and the eigenvalues have the following physical interpretation [18] λ n = P reac n…”
Section: A Radiated Power-based Formulationsupporting
confidence: 78%
“…In the following, we consider only structures with constant ε 1 and Z s . The power quantities can also be expressed with operator inner products [18], [19]…”
Section: Power Orthogonalitymentioning
confidence: 99%
“…For a given operator L, operator M should be defined so that the eigensolutions are related to radiated fields. This guarantees that the far fields of the modes are orthogonal and the complex valued eigenvalues λ n have the following physical interpretation [20], [21] Re(λ n ) =…”
Section: A Theoretical Background and Design Parametersmentioning
confidence: 99%
“…The generalized eigenvalue equation, used to find the characteristic eigenvalues and eigenvectors (eigencurrents) needs to be defined properly to guarantee that the obtained eigensolutions are useful and physically meaningful completely excluding non-physical, so called spurious solutions. This is particularly important for bodies having high dielectric constant and being also highly lossy, such as the human body [20]. Recently we have shown that CMA can be reliably applied for the analysis of combined PEC (antenna) and lossy dielectric (user) structures [21].…”
Section: Introductionmentioning
confidence: 99%
“…Eliminating one of the electric or magnetic current is preferable but not essential. One needs to solve a double sized GEE without eliminating one of the currents [14], [15]. Eliminating one of them would need to perform a matrix inversion [10], but it may be avoided by using the single integral equation formulations [16].…”
Section: Introductionmentioning
confidence: 99%